Eskatologi Puncak: Reorientasi Makna Liqa’ullah sebagai Kenikmatan Transendental dalam Narasi Sejarah Al-Qur'an - Muhammad Rafsanjani; Muhammad Dafa Rizki Muharram; Muhammad Arwani Rofi'i (PT. Student Rihlah Indonesia, 2026)
This study aims to reconstruct the understanding of the nature of paradise in the Qur'an, which is often dominated by materialistic-sensory interpretations. Amidst eschatological discourses that tend to visualize heaven as a space for biological satisfaction, this article offers a reorientation perspective on the concept of Liqa’ullah (encounter with Allah) as the pinnacle of transcendental bliss. Utilizing the maudhu’i (thematic) exegesis method integrated with a phenomenological hermeneutic approach, this research dissects several eschatological verses to uncover the spiritual significance behind material symbols. The results indicate that the Qur'anic narrative regarding physical pleasures (such as rivers, palaces, and pure spouses) functions as a culturallinguistic dialectical instrument for the initial audience, while its ultimate essence lies in the ontological dimension of encountering the Creator. These findings confirm that within the trajectory of faith history, the promise of Liqa’ullah serves as a determinant factor driving the spiritual resilience of prophetic figures. This study implies a paradigm shift in understanding the hereafter, from merely a physical destination to an experience of absolute Divine presence.